Replication Data for: Root traits and their potential links to plant ideotypes to improve drought resistance in common bean. - Polania, Jose; Poschenrieder, Charlotte; Rao, Idupulapati M.; Beebe, Stephen E. (International Center for Tropical Agriculture, 2018)
Root and shoot traits related with drought resistance in common beans. A set of 36 bean genotypes belonging to the Middle American gene pool were evaluated under field and greenhouse conditions under drought stress conditions. Field data on grain yield and other shoot traits measured under drought were related with the greenhouse data on root traits under drought conditions to test the relationships between shoot traits and root traits. Response of root vigor to drought stress appeared to be related with ideotypes of water use (water savers and water spenders). The water spender ideotypes presented deeper root system, while the water saver ideotypes showed a relatively shallower root system.